Arsenic removal from contaminated waters - Adams D.J.; Diaz X.; Mankhand T.R.; Miller J.D.; Pennington P.; Chatwin T. (My University, 2025)
Arsenic is a contaminant at 781 of 1,430 sites identified on the National Priorities List and in mining and mineral processing wastewaters, smelter wastes, and sites for manufacture of semiconductors, petroleum products, wood preservatives, animal feed additives, and herbicides. Arsenic affects ∼4,100 municipal water systems nationwide and is difficult to treat to 10 ppb levels. Adsorptive media can remove up to 99% of arsenic from drinking water at costs for POU/POE applications of ∼$0.20/1,000gal. Full-scale microbial arsenic removal/stabilization treatment costs of $0.10/1,000 gal have been demonstrated for mining and ground waters to 2 ppb levels. Processes using magnetic activated carbon and bacteria/biopolymers; separately and combined (BIOMAC) have been demonstrated to treat high levels of Arsenic (V) to low levels under a wide range of water chemistry. BIOMAC benefits are expected to include other heavy metal removal, such as lead, copper, zinc, fluoride, selenium, and improvement in taste and odor.